How fish can play a stronger role to achieve globally set goals - Thilsted, Shakuntala (2018)
Shakuntala Thilsted IFPRI-FAO conference, "Accelerating the End of Hunger and Malnutrition" November 28–30, 2018 Bangkok, Thailand